2011
DOI: 10.1186/1758-2652-14-35
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of family planning methods and unplanned pregnancies among HIV‐infected individuals: a cross‐sectional survey among clients at HIV clinics in Uganda

Abstract: BackgroundPrevention of unplanned pregnancies among HIV-infected individuals is critical to the prevention of mother to child HIV transmission (PMTCT), but its potential has not been fully utilized by PMTCT programmes. The uptake of family planning methods among women in Uganda is low, with current use of family planning methods estimated at 24%, but available data has not been disaggregated by HIV status. The aim of this study was to assess the utilization of family planning and unintended pregnancies among H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
99
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 11 publications
22
99
11
Order By: Relevance
“…The provision of contraceptives services at the ART clinic to prevent pregnancy is critical, but largely a neglected strategy to prevent motherto-child transmission of HIV and unintended pregnancy (Kaida et al 2010). These findings are in tandem with several studies that reported that a substantial proportion of unplanned pregnancies occur due to contraceptive method failure (Henshaw 1998, Cleland and Ali 2004, Kirshenbaum et al 2004, Wanyenze et al 2011. Although most modern contraceptive methods are highly effective among couples who use them according to prescription (both consistently and correctly), the contraceptives may be less effective during actual or typical use (Cleland andAli 2004, Trussell andWynn 2008).…”
Section: Couples Who Had Children Due To Failure Of Family Planning Msupporting
confidence: 76%
“…The provision of contraceptives services at the ART clinic to prevent pregnancy is critical, but largely a neglected strategy to prevent motherto-child transmission of HIV and unintended pregnancy (Kaida et al 2010). These findings are in tandem with several studies that reported that a substantial proportion of unplanned pregnancies occur due to contraceptive method failure (Henshaw 1998, Cleland and Ali 2004, Kirshenbaum et al 2004, Wanyenze et al 2011. Although most modern contraceptive methods are highly effective among couples who use them according to prescription (both consistently and correctly), the contraceptives may be less effective during actual or typical use (Cleland andAli 2004, Trussell andWynn 2008).…”
Section: Couples Who Had Children Due To Failure Of Family Planning Msupporting
confidence: 76%
“…Many of the women (and their partners) maintain a profile of unplanned fertility, regardless of their HIV diagnosis. The result is consistent with studies showing that positive HIV status is not necessarily associated with a decrease in unplanned pregnancy 27,29,30,31 .…”
Section: Discussionsupporting
confidence: 82%
“…In a similar study conducted in Uganda [11], 53% of HIV-positive women reported that they did not plan their current or last pregnancy. This may suggest that a substantial number of pregnancies among HIV-positive women are unintended and may be unwanted.…”
Section: Discussionmentioning
confidence: 99%